Evaluation of the effect of patient's age on the tooth response to electric pulp test - Jalil Modaresi; Vahid Shirani; Mohammad Malekzadeh (Tehran University of Medical Sciences, 2014)
Background and Aims: Electric pulp tester is a valuable instrument to examine tooth's pulp vitality. There is no agreement about the response of immature teeth to electric pulp tester and the reason is expressed as the failure of nerve fibers' development. The aim of this study was to investigate the effect of patient's age on the tooth response to electric pulp tester.   Materials and Methods: In this cross-sectional study, 300 maxillary central permanent teeth in 150 volunteers were examined by using electric pulp tester. The volunteers were classified in 5 age groups of 7-8, 9-10, 11-12, 13-4, and 30-35; and teeth lacking sound and healthy pulp were excluded. Data were analyzed using SPSS-16 software, one-way analysis of variance, and Tukey post hoc test.   Results: The average response to electric pulp tester in age groups of 7-8, 9-10, 11-12, 13-4, and 30-35 years old were 2.9±0.1, 2.8±0.1, 2.3±0.1, 2.2±0.1 and 1.8±0.1 ,respectively. This indicated that by increasing teeth age, they responded to lower level of electric pulp tester. In subjects less than 14 years old, there was no significant difference between neighboring groups (P=0.3); however, a significant difference was observed between subjects less than 14 years old and adults (P<0.001).   Conclusion: This study showed that immature teeth responded at higher levels to electric test; however, all teeth responded to electric pulp tester.